Studies on special strain gage configuration for evaluation of existing stress in concrete structures by hole drilling technique - Parivallal, S.; Ravisankar, K.; Nagamani, K. (Journal of Structural Engineering, 2024)
Assessing the existing level of stress in prestressed concrete structures in service is fairly a diffi cult task and the engineers are often faced with lack of actual design/construction information and environmental service conditions. Determination of in-situ stress in the concrete surface is one way to assess the stress available in the prestressed concrete members. This paper describes the development of a method for measurement of existing stress on concrete structures subjected to biaxial stress condition. A special strain gage configuration consisting of six strain gages placed in radial and tangential orientation around the intended hole is considered. Combining the radial and tangential gages in a half bridge whetstone bridge circuit can improve the stress measurement accuracy when using the hole drilling method. Different positions of sensor locations were checked for its effective strain sensitivity and accuracy and optimum configuration was chosen by using closed form through hole plate analysis. The calibration constants for the chosen configuration were evaluated for different core depths using finite element analysis to assess the existing stress in concrete structural members.